The four Rs performance indicators of water distribution networks: A review of research literature. Issue 5 (2nd May 2017) - Gunawan, Indra; Schultmann, Frank; Zarghami, Seyed Ashkan
Abstract : Purpose: The purpose of this paper is to review the different interpretations of four key performance indicators of water distribution networks (WDNs): reliability, resilience, redundancy and robustness. It then addresses a range of metrics which have been developed to assess the performance of critical infrastructures, in particular WDNs. Design/methodology/approach: The paper provides a comprehensive review and categorization of performance indicators of WDNs. The main focus is on papers addressing performance indicators of water distribution systems, additionally papers on application of complex system approach to critical infrastructures are also included. Findings: Due to this complexity, a wide range of interpretation of WDNs performance indicators exists in the literature. This represents a significant impediment toward universally accepted interpretation of these indicators Accurate assessment of WDNs' performance depends on clear definition of system performance indicators as well as accurate quantifying of these indicators. The application of 18 metrics as a basis for assessing the system performance have been reviewed in this paper and none are particularly significant as standalone values. Combination of these indicators are required to accurately indicate the performance of WDNs. Originality/value: The authors believe that this paper can be a valuable source of information for academic researchers and practitioners and suggests a roadmap for future works.